Perbedaan Tingkat Kecenderungan Depresi pada Akseptor Berbagai Jenis Kontrasepsi Hormonal di Puskesmas Sumbersari Kabupaten Jember (The Difference of Depression Tendency Level on User of Several Hormonal Contraception Types in Sumbersari Primary Health Care, Jember) - Ghuiranda S Ramadhan; Alif Mardijana; Hairuddin Hairuddin (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Hormonal contraception is a method to prevent pregnancy that contains synthetic progesterone and estrogen. There are three types of hormonal contraception, i.e injection, pill, and implant. The side effect of hormonal contraception is depression. The aim of this research was to determine the difference of depression tendency level on several hormonal contraception types in Sumbersari Primary Health Care, Jember. This research method was analitical observational with cross sectional approache. Sample total were 103 hormonal contraception's acceptors who were recruited by proportionate stratified random sampling technique. Sample were interviewed using Hamilton Depression Rating Scale (HDRS) as the screening depression tendency level. Kruskal wallis statistical test showed significance point 0,00 (p<0,05). Post Hoc analysis with Mann-Whitney test between pill and injection acceptors group showed significance point 0,001 (p<0,05), 0,001 (p<0,05) for injection and implant acceptors group, then 0,000 (p<0,05) for pill and implant. In conclusion there is significance difference of depression tendency level in several types of hormonal contraception in Sumbersari Primary Health Care, Jember. Keywords: depression tendency level, hormonal contraception, HDRS